?TOXIC EFFECTS OF ZINC ONDIFFERENT TREE SEEDLINGS (Biological Sciences - PJSIR, 1999)
Asignificantreduction inseedgermination,seedlinggrowthanddryweightofAlbizia lebbeck, Peltophorum pterocarpum. and Thespesia populnea was noted when zinc concentration was increased. A significant reduction (p